A legal analysis of labour dispute prevention and resolution under individual employment law in Zambia: Willard Mutoka v Chambeshi Water and Sewerage Company Limited (Comp. IRCLK/382/2018) - Kasonde, Clement; Chitengi, Justine Sipho (Obiter, 2020)
This case note is a legal review and analysis of Willard Mutoka v Chambeshi Water and Sewerage Company Limited, a Zambian case relating to a labour dispute under the individual employment law sphere. The authors/reviewers herein were retained as counsel for the respondent company in the matter in casu. Appreciating that Zambia has both individual and collective labour dispute prevention and resolution mechanisms, the authors/reviewers in consultation with all parties involved opted to pursue the alternative dispute resolution approach under the High Court for Zambia (Amendment) Rules, 1997 (Court-Annexed Mediation Order XXXI Rule 4), instead of litigation, resulting in the faster, cheaper and final settlement of the case in full satisfaction and accord of both parties as discussed hereinafter. Unlike arbitration awards which are conclusive and final, mediation agreements or settlements need to be registered in the courts for them to be recognised as binding.